Male and female cichlid fish show cognitive inhibitory control ability - Brandão, Manuela Lombardi [UNESP]; Fernandes, Ana Marina Tabah de Almeida [UNESP]; Gonçalves-de-Freitas, Eliane [UNESP] (Springer Nature, 2019)
Inhibitory control is a way to infer cognitive flexibility in animals by inhibiting a behavioral propensity to obtain a reward. Here we tested whether there are differences in inhibitory control between females and males of the fish Nile tilapia owing to their distinct reproductive roles. Individuals were tested under a detour-reaching paradigm, consisting of training fish to feed behind an opaque barrier and, thereafter, testing them with a transparent one. Fish is expected to avoid trying to cross through the transparent barrier to achieve food (reward), thus showing inhibitory control by recovering the learned detour with the opaque apparatus. Both males and females learned to detour the transparent barrier with similar scores of correct responses, whereas females reached the food faster. This result is probably associated to their different sex roles in reproduction: females care for the eggs and fry inside their mouth (thus requiring a high inhibitory control not to swallow them), whereas males have to stay inside the territory defending it against intruder males, which also demands some inhibitory ability not to leave the spawning site and take the risk of losing it. Furthermore, this evidence of cognitive flexibility can enable social fish to deal with unpredictable interactions.